(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nowadays human impact to habitats and species are stronger then ever before. Latvia is typical example of fragmented landscape, where forest patches are mixed with agricultural land and waterbodies. Latgale is one of typical such a fragmented landscape parts of Latvia. Around 6.41 % of Latgalian forests were evaluated as Woodland Key Habitats (WKHs) or potential WKHs (P)WKHs after WKH inventory. In total 16 WKH types, suitable for bryophyte and lichen indicator species existence were identified in Latgale. (P)WKH type, forest stand age and area were significant factors influencing bryophyte and lichen specialist and indicator species richness in forest stand level. WKH status did not provide any official conservation status for habitats or species based on current legislation in Latvia. Therefore establishment of conservation areas as microreserves for habitats and species and Nature Reserves in areas, with high (P)WKH density is an effective tool for their long-term conservation in Latgale. Further scientific studies of bryophytes, lichens and WKHs are necessary for planning the best conservation scenarios taking into account also forest ecosystem services.